(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
There has recently been an increasing interest in water treatment methods as a result of growing concerns over shortages of clean water. This paper aims to review the past and present researches on chitosan for the adsorption of heavy metals from the wastewater. Adsorption is considered to be the most efficient method for the removal of metal impurities from drinking water. Chitosan, a deacetylated derivative of chitin, has many commercial applications due to its biocompatibility, nontoxicity, and biodegradability. Moreover, amine groups are present on the backbone of chitosan. For this reason, chitosan has been used for the adsorption of heavy metals. To begin with, mechanism of adsorption of heavy metal ions on chitosan and disadvantages of heavy metal ions were reviewed. Further, a detailed review had been done on the adsorption capacities of crosslinked chitosan, chitosan nanofibers, chitosan nanoparticles, chitosan composites, modified/pure chitosan, and porous chitosan. Lastly, research gaps and future recommendations were given for further development and accurate results of adsorption.